(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The article presents the results of the theoretical studies on the justification of the angle of installation in relation to the direction of movement of the improved harrow leveller. According to it, in order to ensure free sliding of soil pieces along the working surface of the soil leveler, its installation angle of installation in relation to the direction of movement should be less than 55°.